Efektivitas Dan Efisiensi Pembiayaan Pendidikan Pasca Covid-19 - Rizal Hidayat; Mufthi Alam; Achmad Syarief Halim; Sukri Agustian (Cetta: Jurnal Ilmu Pendidikan, 2023)
During the Covid-19 transition period, there were many transitions that had to be made again, one of which was regarding education financing which is a crucial matter within the scope of developing educational institutions/schools. It is undeniable that from the existing reality there are always problems and obstacles regarding financing education during and after Covid 19, causing educational institutions to prioritize budgets to facilitate the running of the educational environment, especially during the Covid period there were still schools that were not maximal in financing as a result learning uncertainty. This study aims to determine the effectiveness and efficiency of educational financing carried out during the post-covid-19 period so that educational institutions can allocate educational funds as best as possible without burdening students and parents. The method used is the method of literature study. With a philosophical inquiry approach. The results of the research show that, in order to achieve good financing, schools need to understand financial management by looking at the effectiveness and efficiency that is carried out. That way schools don't need to squander a lot of the budget they do. Educational institutions must really understand the effectiveness of financing, by understanding education financing both macro (national) and micro (school) arrangements, as well as several types of educational costs such as direct costs, indirect costs, personal costs. (private costs) social costs (social costs), costs in the form of money (monetary costs) and costs that are not in the form of money (non-monetary costs). The results of managing education costs so that they become effective and efficient management can be seen from internal efficiency which must produce the desired output at maximum cost and external efficiency. This can be seen from the ratio between financial benefits as a result of Education with all costs incurred for the education process.